Development and Testing of Complex Molecular Genetic Diagnosis of Genitourinary System Neoplasms - Telegeev, G.; Polishchuk, L.; Lisecka, T.; Shvachko, L.; Dybkov, M.; Stakhovsky, O.; Vitruk, І.; Stakhovsky, E. (Science and Innovation, 2024)
A system for comprehensive non-invasive diagnostic of urogenital system neoplasms has been designed and tested on the basis of molecular genetic parameters (the tmprss2/erg rearrangement using reverse transcriptase polymerase chain reaction (PCR), the level of psa3/psa and cxcr4 gene expression using quantitative PCR, and the gstp1 gene promoter methylation status using methyl-specific PCR.